Intravitreal 0.19 mg fluocinolone acetonide implant in non-infectious uveitis - Hikal, Muaas; Celik, Nil; Auffarth, Gerd U.; Kessler, Lucy Joanne; Mayer, Christian; Khoramnia, Ramin (Journal of Clinical Medicine, 2021)
The efficacy of the 0.19-mg fluocinolone acetonide (FAc) intravitreal implant (ILUVIEN) in the treatment of non-infectious uveitic macular edema (UME) was assessed on twenty-six patients (34 eyes) with non-infectious UME between 2013 and 2020, in a mean follow-up of 18 ± 19.3 (mean ± SD) months. Macular edema was resolved in 24 (70.6%) cases. Five of these eyes had a relapse after 23.2 ± 14 months. Three FAc reinjections were performed and a drying of the macula was observed. After FAc implantation, 24 eyes (70.6%) were completely dry; central retinal thickness (CRT) decreased in 6 eyes (17.6%), but residual intraretinal fluid was still evident. In 20 eyes (58.5%), visual acuity (VA) improved (from +1 to +5 lines) and remained stable in 9 eyes (26.5%). Thirty eyes (88.2%) were pseudophakic at baseline and four were phakic. Three of these eyes had a cataract prior to therapy and the other developed a cataract 2.5 years after the FAc implant was administered. There was an overall increase in intraocular pressure (IOP; +4.4 ± 3.7 mmHg) and eye drops were required in three eyes. The FAc implant led to long-term improvements in mean CRT and VA, and that the side-effect profile was manageable in a clinical setting in patients with non-infectious UME.
Gesehen am 18.10.2021